2014
DOI: 10.1111/bjh.13221
|View full text |Cite
|
Sign up to set email alerts
|

Survival of AIDS‐related diffuse large B‐cell lymphoma, Burkitt lymphoma, and plasmablastic lymphoma in the German HIV Lymphoma Cohort

Abstract: SummaryOverall survival (OS) of patients with acquired immunodeficiency syndrome (AIDS)-related Burkitt lymphoma (BL), diffuse large B-cell lymphoma (DLBCL) and plasmablastic lymphoma (PBL) was analysed in the German AIDS-related-Lymphoma-Cohort-Study. Of 291 patients prospectively included between January 2005 and December 2012, 154 had DLBCL, 103 BL and 34 PBL. Two-year OS rates were similar between BL (69%) and DLBCL patients (63%) but lower for PBL patients (43%). Intermediate (Hazard ratio [HR] 4Á1 95% co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 15 publications
5
40
1
3
Order By: Relevance
“…[911] Cohort studies suggest that plasmablastic lymphoma has an inferior survival to Burkitt and DLBCL. [12] We demonstrate that PBL may be curable, even in patients with higher stage disease and more extranodal involvement compared to the cases described by Delecluse, et al where the disease was primarily localized to the jaw in the majority of patients.…”
mentioning
confidence: 48%
“…[911] Cohort studies suggest that plasmablastic lymphoma has an inferior survival to Burkitt and DLBCL. [12] We demonstrate that PBL may be curable, even in patients with higher stage disease and more extranodal involvement compared to the cases described by Delecluse, et al where the disease was primarily localized to the jaw in the majority of patients.…”
mentioning
confidence: 48%
“…In the German AIDS-Related Lymphoma Cohort Study, the 2-year overall survival (OS) was reported to be 63% [14].…”
Section: Diffuse Large B-cell Lymphomamentioning
confidence: 99%
“…Plasmablastic lymphoma (PBL) has been estimated to account for less than 3-12% of all HIV-related lymphomas [14,31] featuring a lack of CD20 expression and generally high expression of CD138, a well-differentiated plasma cell marker [32]. Due to its very aggressive clinical course and the disappointing outcome with CHOP or CHOP-like regimens, more intensive chemotherapy protocols have been suggested such as the B-ALL/NHL protocol, CODOX-M/ IVAC, or consolidation with high-dose (HD) chemotherapy and subsequent autologous stem cell transplantation (SCT).…”
Section: Plasmablastic Lymphomamentioning
confidence: 99%
“…Several clinical trials (17)(18)(19)(20)(21) and observational studies (22)(23)(24) with HIV-infected lymphoma cases treated with HAART reported survival outcomes comparable to general patients with lymphoma. However, a few studies directly compared HIV-infected and HIV-uninfected patients with lymphoma and found inconsistent results.…”
Section: Introductionmentioning
confidence: 99%